Thrombose spontanée d’une varicocèle droite à propos d’un cas - ADJADOHOUN Sonia Bignon Mahussi Gwladys; KIKI Miralda Sessi; AKANNI Djivèdé Witchèkpo Maurice Mohamed; ADJOVI Boris; NGAMO Gabriel; YEPKE AHOUANSOU Patricia; SAVI de TOVE Koffi Mensa; BIAOU Olivier, (Journal Africain d Imagerie Médicale (J Afr Imag Méd) Journal Officiel de la Société de Radiologie d’Afrique Noire Francophone (SRANF), 2020)
Introduction: Spontaneous varicocele thrombosis is rare. Only 20 cases have been recorded worldwide since the first description of the condition in 1935 by Mc Gavin. Its diagnosis is made difficult by the similarity of its clinical manifestations with other acute scrotal diseases. The authors report a case of spontaneous varicocele thrombosis revealed by acute scrotal pain in a young man, in which they present a review of the diagnostic elements and therapeutic modalities. Observation: The case involved a 36-year-old young man with no particular medical or surgical history, who had been seen for intermittent right testicular pain that had been evolving for 4 days before his admission, without any notion of fever or trauma. The clinical examination noted only an indurated and painful right spermatic cord. The diagnosis of spontaneous varicocele thrombosis was made by Doppler ultrasonography of the bursae which noted non-compressible dilatation of the right pampiniform venous plexus with the presence of echogenic thrombotic endoluminal material and an absence of Doppler flow. The treatment instituted was drug conservative. Conclusion: Although acute scrotal disorders are mostly classified as surgical emergencies, the diagnosis, typically radiological, of spontaneous varicocele thrombosis preferably implies conservative treatment with good results. RÉSUMÉ Introduction : La thrombose spontanée d’une varicocèle est rare. Seuls 20 cas ont été répertoriés de par le monde depuis la première description de la pathologie faite en 1935 par Mc Gavin. Son diagnostic est rendu difficile par la similitude de ses manifestations cliniques avec d’autres affections scrotales aigues. Les auteurs rapportent un cas de thrombose spontanée d’une varicocèle révélée par une douleur scrotale aigue chez un jeune homme, à l’occasion duquel ils présentent une revue des éléments du diagnostic et des modalités thérapeutiques. Observation : Il s’agissait d’un jeune homme de 36 ans sans antécédent médico-chirurgical particulier, ayant consulté pour des douleurs testiculaires droites intermittentes évoluant depuis 4 jours avant son admission, sans notion de fièvre ni de traumatisme. L’examen clinique n’a noté qu’un cordon spermatique droit induré et douloureux. Le diagnostic de thrombose spontanée d’une varicocèle a été posé par l’échographie Doppler des bourses qui a noté une dilatation non compressible du plexus veineux pampiniforme droit avec présence d’un matériel endoluminal thrombotique échogène et une absence de flux doppler. Le traitement instauré était conservateur médicamenteux. Conclusion : Bien que les affections scrotales aigues soient pour la plupart classées au rang des urgences chirurgicales, le diagnostic, typiquement radiologique, d’une thrombose spontanée de varicocèle implique préférentiellement un traitement conservateur avec de bons résultats.